Evaluation of Accuracy of DIAGNOdent in Diagnosis of Primary and Secondary Caries in Comparison to Conventional Methods - Nokhbatolfoghahaie, Hanieh; AliKhasi, Marzieh; Chiniforush, Nasim; Khoei, Farzaneh; Safavi, Nassimeh; Yaghoub Zadeh, Behnoush (Journal of Lasers in Medical Sciences, 2013)
Introduction: Today the prevalence of teeth decays has considerably decreased. Related organizations and institutions mention several reasons for it such as improvement of decay diagnostic equipment and tools which are even capable of detecting caries in their initial stages. This resulted in reduction of costs for patients and remarkable increase in teeth life span. There are many methods for decay diagnostic, like: visual and radiographic methods, devices with fluorescence such as Quantitative light-induced fluorescence (QLF), Vista proof, Laser fluorescence (LF or DIAGNOdent), Fluorescence Camera (FC) and Digital radiography. Although DIAGNOdent is considered a valuable device for decay diagnostic, there are concerns regarding its efficacy and accuracy. Considering the sensitivity of decay diagnosis and the exorbitant annual expenses supported by government and people for caries treatment, finding the best method for early caries detection is of the most importance. Numerous studies were performed to compare different diagnostic methods with conflicting results. The objective of this study is a comparative review of the efficiency of DIAGNOdent in comparison to visual methods and radiographic methods in the diagnostic of teeth occlusal surfaces. Methods: Search of PubMed, Google Scholar electronic resources was performed in order to find clinical trials in English in the period between 1998 and 2013. Full texts of only 35 articles were available. Conclusion: Considering the sensitivity and specificity reported in the different studies, it seems that DIAGNOdent is an appropriate modality for caries detection as a complementary method beside other methods and its use alone to obtain treatment plan is not enough.